Can the fine wheat bran be a betaine source in poultry diets? - Somensi, Marcelo Luiz (2019)
The effect of fine wheat bran (FWB) as a methyl donor source on performance, metabolism, body composition and blood traits of growing broilers was studied. Three hundred and twenty broilers from eight to 28 d of age, distributed in a randomized block design, with five treatments and eight replicates of eight animals each were used. The experimental diets were: NC, formulated with 72% of the Met+Cys requirement; Met, formulated with 85% of the Met+Cys equivalents by DL-methionine addition; Bet, formulated with 85% of the Met+Cys equivalents by anhydrous betaine addition; Fwb- , formulated with 72% of the Met+Cys requirement and 20% FWB; and Fwb+, formulated with 85% of the Met+Cys requirement and 20% FWB. Feed intake was reduced (p<0.05) by FWB inclusion but the feed conversion ratio was the same (p>0.05) between the positive control diets. Supplementation of DL-methionine and anhydrous betaine showed the same (p>0.05) metabolizability of nutrients. Treatments with higher DL-methionine levels (Met and Fwb+) promoted more weight of feathers (p<0.05). Animals fed with FWB showed the lowest (p<0.05) body gains. In conclusion, FWB inclusion did not promote methyl radicals supply.